(untitled) (Asian Journal of Medical Sciences, 2019)
Background: The whole plant of Coccinia indica is very effective in different types of diseases with fewer side effects. The leaves, roots of this plant were claimed to be useful in the treatment of diabetes mellitus based on folk medicine. The purpose of this study was to examine the antihyperglycemic effect of water extract of C. indica in alloxan diabetes rats. Aims and Objectives: The aim of this study is to find whether the conditions, hyperglyclemia and hyerlipidemia, are correlated and whether the application of the aqueous extract leads to abating these two conditions. Materials-Methods: The aqueous leaves extracts of C. indica (200 mg/kg) were administered orally for 14 days, in alloxan induced diabetic rats on Glucose, Lipid profile, Lipoproteins and Lipid metabolizing enzymes activity. Result: The aqueous leaves extract of C. indica induced significant improvement in glucose, serum Lipids, lipoproteins and lipid metabolizing enzyme activity (HMG CoA reductase, LCAT). Conclusion: The present study indicates that the extract of Coccinia indica exhibits lipid lowering, maintaining lipoproteins concentration and also improves the activities of lipid metabolizing enzyme in hyperglycemic rats leading to an increase in peripheral glucose consumption.